Disrupting Biofilms From Titanium with a CHG Antimicrobial Irrigation System. Issue 4 (November 2022) - Eberle, Tanya; Sanders, Jessica; Laubach, Isabel; Manser, Jak; Davis, Troy; Peterson, Marnie; Twomey, Carolyn L.
Category: Other Introduction/Purpose: Orthopedic device-related infections can be difficult to treat and decrease the success of surgical interventions. The implant provides a surface for bacterial attachment and biofilm formation, which decreases antimicrobial efficacy. This study was conducted to assess the ability of the Chlorhexidine Gluconate (CHG) Antimicrobial Irrigation System to disrupt biofilms from titanium coupons using an adapted ASTM E2871-19 method, 'Standard Test Method for Determining Disinfectant Efficacy Against Biofilm Grown in the CDC Biofilm Reactor Using the Single Tube Method.' Methods: CDC Biofilm Reactor was inoculated with Staphylococcus epidermidis (ATCC 14990 TM ), methicillin-resistant Staphylococcus aureus (ATCC 43300 TM ), Pseudomonas aeruginosa (ATCC 15442 TM ), or Escherichia coli (ATCC 25922 TM ). The reactors were run in a batch phase for 24 h, followed by continuous flow phase for an additional 24 h to produce single-species biofilms on titanium coupons. After coupons were washed with PBS to remove planktonic bacteria, growth control coupons were placed into standard sampling solution with 1% Tamol (SST) (neutralizer) or treated with CHG Antimicrobial Irrigation System according to Instructions for Use (IFU) followed by a 60 sec dwell or no dwell. Coupons were rinsed with normal saline following treatment and placed in SST. Then coupons were sonicated and vortexed to release bacteria and plated for enumeration. A coupon from each group was fixed for SEM imaging. Results: The CHG Antimicrobial Irrigation System disrupted biofilms of all organisms from titanium coupons with the greatest log reduction per coupon in the 60 sec dwell treatment group (log10 reduction 2.02 to 4.56 CFU/coupon from controls) (Table). Overall, S. epidermidis and E. coli biofilms had the greatest reductions in bacterial densities. SEM images confirmed biofilm disruption from the titanium surface. Conclusion: his study determined that the CHG Antimicrobial Irrigation System disrupted biofilms from titanium coupons when used according to the instructions for use.